Locational analysis centralized provincial bus terminals in Metro Manila - Buzon, Carl John C.; Flores, Franz Kristopher S.
The presence of provincial buses plying the thoroughfares of Metro Manila is identified as one of the chief causes of congestion especially in EDSA. To address this concern, the government has issued the mandate to pursue the Integrated Transport System (ITS) project which proposes to create intermodal transport terminals with locations in the North and South of Metro Manila thereby relocating and reorganizing the existing provincial bus terminals. This requires selecting suitable locations on where the terminals will be built. The provincial bus passengers, provincial bus operators and involved government agencies comprise of the major stakeholders in the ITS projects. As such, it is important to account their needs in the terminal site selection process. This research aims to develop a set of criteria in selecting locations in Metro Manila for centralized provincial bus terminals (used interchangeably with ITS terminals) by determining the main considerations of the stakeholders and consolidating them. This set of criteria will then be applied to the government-proposed locations of centralized provincial bus terminals as means of assessment. Data gathered consists of surveys and interviews conducted to the stakeholders and reconnaissance surveys at the proposed sites. In the assessment, it is found that the proposed location for the northbound terminal in North Triangle is not viable because of its placement not at the fringes and the heavy congestion existing in the immediate vicinity. On the other hand, the location for the southbound terminal proposed to be at the FTI Complex appears as a suitable site as it passes the developed set of criteria.